Biodiversity in European agricultural landscapes: transformative societal changes needed. (December 2021) - Mupepele, Anne-Christine; Bruelheide, Helge; Brühl, Carsten; Dauber, Jens; Fenske, Michaela; Freibauer, Annette; Gerowitt, Bärbel; Krüß, Andreas; Lakner, Sebastian; Plieninger, Tobias; Potthast, Thomas; Schlacke, Sabine; et al.
Abstract : Reversing the decline of biodiversity in European agricultural landscapes is urgent. We suggest eight measures addressing politics, economics, and civil society to instigate transformative changes in agricultural landscapes. We emphasize the need for a well-informed society and political measures promoting sustainable farming by combining food production and biodiversity conservation